Modeling a PV-FC-Hydrogen Hybrid Power Generation System - Javadpoor, S.; Nazarpour, D. (Engineering, Technology & Applied Science Research, 2017)
Electrical grid expansion onto remote areas is often not cost-effective and/or technologically feasible. Thus, isolated electrical systems are preferred in such cases. This paper focuses on a hybrid photovoltaic (PV)-hydrogen/fuel cell (FC) system which basic components include a PV, a FC, alkaline water electrolysis and a hydrogen gas tank. To increase the response rate, supercapacitors or small batteries are usually employed in such systems. This study focuses on the dynamics of the system. In the suggested structure, the PV is used as the main source of power. The FC is connected to the load in parallel with the PV by a transducer in order to inject the differential power while reducing power generation in relation to power consumption. An electrolyzer is used to convert the surplus power to hydrogen. This study studies a conventional hybrid photovoltaic-hydrogen/fuel cell system to evaluate different loading behaviors. Software modeling is done for the suggested hybrid system using MATLAB/SIMULINK.